The Impact of Investment Technology, Hedging, Corporate Governance, Growth, and Capital Structure on Firm Value: The Moderating Role of Financial Performance in Indonesian Banks (2014-2018) - Suherminingsih, Maria (Indonesian Management and Accounting Research, 2022)
This study analyzes the influence of investment technology, hedging, corporate governance, growth, and capital structure on firm value in Indonesian banks listed on the Indonesia Stock Exchange (IDX) from 2014 to 2018, moderated by financial performance. Through quantitative methods and regression analysis, the research demonstrates that investment in technology negatively impacts firm value, whereas hedging and capital structure positively influence it. Conversely, corporate governance, growth, and financial performance do not significantly influence firm value. Furthermore, financial performance strengthens the relationship between investment technology and firm value but does not significantly moderate the effects of hedging, corporate governance, growth, or capital structure on firm value. The findings suggest banks should optimize investment technology, hedging strategies, and capital structure to enhance firm value.